Impact of Pulmonary Rehabilitation on Hospitalization Duration, IL-6 Levels, and Respiratory Muscle Power in Hospitalized Community-Acquired Pneumonia Patients - Santony Santony; Iin Noor Chozin; Teguh Rahayu Sartono; Rahmad Rahmad; Harun Al Rasyid (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2022)
Background: Pneumonia is acute inflammation of the lung parenchyma. The long duration of hospitalization is associated with increased morbidity, nosocomial infections and treatment costs. Methods: The study was conducted from May to November 2019 at Saiful Anwar Hospital, Malang, with 40 pneumonia patients in the non-intensive community inpatient room divided into 2 groups. The treatment group performed pulmonary rehabilitation measures consisting of breathing exercise, effective coughing techniques, clapping, postural drainage and respiratory muscle training using spirometry incentives. Results: The duration of hospitalization for the treatment group was 2.25 days shorter (p<0.001). The average IL-6 level in the 5th day of the treatment group was lower than without treatment, that was 54.43 pg/ml (p=0.221). The mean of pressure threshold loading in the group without treatment was 31.5 cmH2O on first day and 36.35 cmH2O on the 5th day (p <0.001) and on first day treatment group was 32.9 cmH2O and 39.35 cmH2O on the 5th day (p=0.001), and the mean value of the 5th day of the treatment group was higher than without treatment (P=0.015). the mean of the 5th day of the treatment group was higher than without treatment (p=0.06).Conclusion: Pulmonary rehabilitation as adjunctive therapy shortens the duration of hospitalization. In both groups there was a decrease in IL-6 levels on the 5th day compared to zero and the lower IL-6 levels were not significant in the treatment group. There was a significant increase in the value of pressure threshold loading inspiration and expiration day fivecompared to day zero in the two groups and there was a significant increase in the Pressure Threshold Loading Inspiration mean treatment group compared to no treatment on the 5th day, but the Pressure Threshold Loading Expiration rate showed no significant increase.